Serendipitous Conversion of an Acetylamino Dideoxy-Octonic Acid Derivate into a Functionalized Carbohydrate–Pyrazole Conjugate and Investigation of the Method´s General Applicability - Jelena K. Berl; Christian Czaschke; Ann-Kathrin Pramor; Christian B. W. Stark; Joachim Thiem (Molecules, 2024)
By treatment of the peracetylated methylester of 4-acetylamino-2,4-dideoxy-d-glycero-d-galacto-octonic acid (ADOA-PAE) with nitrosyl tetrafluoroborate, a serendipitous formation of a highly functionalized carbohydrate–pyrazole conjugate was observed in 95% yield. This observation is remarkable, as it involves a five-step one-pot synthesis that proceeds via an 1,3-acyl shift and a 1,5-electrocyclization, which usually requires thermal conditions; however, the reaction occurred at a temperature of 0 °C. Additionally, the excellent yield of the carbohydrate-decorated pyrazole and the regiospecificity of the cyclization are of particular interest, as regioselectivity is always a challenge in pyrazole synthesis. Subsequently, this novel access to pyrazoles starting from N-acetyl-allyl amides via nitrosation and electrocyclization was investigated. In addition, mechanistic studies for the formation of substituted pyrazoles of type were carried out.